PENINGKATAN PELAKSANAAN PENGAWASAN OLEH PENGAWAS TK/SD DI KECAMATAN TIGO NAGARI KABUPATEN PASAMAN - Anrizal (Universitas Negeri Padang, 2014)
This study aims to describe the implementation of supervisory tasks kindergarten / elementary school in the District Tigo Nagari, and describes the obstacles that may be encountered in the implementation of the supervision and put forth the effort that may be made ​​by the supervisor kindergarten / elementary school to improve supervision in the District Tigo Nagari. After an examination of the supervisory TK / SD District of Tigo Nagari, it can be concluded that the lack of effective supervisory done it can be seen from the lack of supervision is carried out by the passage of such supervisory managerial supervision and academic supervision.